Prevalence and Risk Factors of Feline Immunodeficiency Virus and Feline Leukemia Virus Infection in Healthy Cats in Thailand - Sprißler, Fabienne; Jongwattanapisan, Prapaporn; Luengyosluechakul, Supol; Pusoonthornthum, Rosama; Reese, Sven; Bergmann, Michèle; Hartmann, Katrin (Frontiers in Veterinary Science, 2022)
The aim of the present study was to determine the prevalence of feline immunodeficiency virus (FIV) and feline leukaemia virus (FeLV) in healthy outdoor cats in North, Northeast and Central Thailand. So far, there has been no study published on the retrovirus prevalence of healthy cats in Thailand in a larger geographic area. In addition, risk factors for FIV and FeLV infections were evaluated. Two hundred sixty healthy cats were prospectively recruited. They originated from 13 locations in North, Northeast, and Central Thailand and were presented for either preventive health care and/or neutering. In each cat, a physical examination was performed to confirm health status. FIV and FeLV status was determined using a commercial rapid enzyme-linked immunosorbent assay (ELISA) (SNAP Combo Plus FeLV/FIV, IDEXX). Risk factors were analysed by hierarchic cluster analysis. Samples of 15/260 (5.8%) cats were positive for FIV antibodies, and 11/260 (4.2%) cats were positive for FeLV antigen. One of 260 (0.4%) cats was positive for both, FIV and FeLV infection. In cluster analysis, no parameter was associated with a higher risk for FeLV infection. However, cats had a significantly (p = 0.026) higher risk for FIV infection when they were 2 years or older, male, intact, privately owned (when compared to feral), from urban (rather than from rural) regions, from Central Thailand (and not from North or Northeast Thailand), were presented for neutering (and not for general health check), had contact to dogs, drank out of puddles and ate raw meat (such as mice). FIV and FeLV infections are endemic in healthy cats in North, Northeast and Central Thailand, but prevalence was lower than expected. Risk factors of FIV and FeLV infection were different, confirming that FIV mainly is an infection of older male intact hunting cats.